Feedback equilibria in a dynamic renewable resource oligopoly: pre-emption, voracity and exhaustion - Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
We extend Fujiwara's (2008) model to describe a differential oligopoly game of resource extraction under static, linear feedback and nonlinear feedback strategies, generalising his result that steady state feedback outputs are lower than monopoly and static oligopoly equilibrium outputs for any number of firms. Additionally, we show that (i) feedback rules entail resource exhaustion for a finite number of firms; and (ii) feedback strategies are more aggressive than static ones as long as the resource stock is large enough, in accordance with the acquired view based on the traditional pre-emption argument associated with feedback information.
Keywords: C73; L13; Q2; 330